2011
DOI: 10.1038/modpathol.2010.227
|View full text |Cite
|
Sign up to set email alerts
|

Regional immunity in melanoma: immunosuppressive changes precede nodal metastasis

Abstract: In order to characterize the degree of immunosuppression in regional immunity in patients with melanoma, we used immunohistochemistry to analyze markers of T-cell subtype and polarity, costimulation, dendritic cell maturation, monocytes, lymphatic vasculature, and angiogenesis. Specifically, we analyzed expression of CD4, CD8, CD14, CD40, CD86, CD123, HLA-DR, IL-10, LYVE, VEGFR3, and VEGF-C in lymph nodes. We compared sentinel lymph nodes with and without metastasis from patients with melanoma with both infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 59 publications
(49 reference statements)
2
52
2
5
Order By: Relevance
“…This is the first study to analyze whole-genome gene expression profiling in SNB samples. Broad defects affecting different immunologic components have been extensively documented in SNs with respect to nontumor-draining nodes, including a decreased frequency of CD8 þ effector T cells, a reduced presence of stimulatory CD86 þ and CD11c þ DCs, and increased Foxp3 density and Th2 cytokine levels (7,11,(32)(33)(34)(35)(36)(37). Our findings partially contradict such observations because we found that immune dysfunction is detected in tumor-positive SNBs in association with disease progression.…”
Section: Discussioncontrasting
confidence: 57%
“…This is the first study to analyze whole-genome gene expression profiling in SNB samples. Broad defects affecting different immunologic components have been extensively documented in SNs with respect to nontumor-draining nodes, including a decreased frequency of CD8 þ effector T cells, a reduced presence of stimulatory CD86 þ and CD11c þ DCs, and increased Foxp3 density and Th2 cytokine levels (7,11,(32)(33)(34)(35)(36)(37). Our findings partially contradict such observations because we found that immune dysfunction is detected in tumor-positive SNBs in association with disease progression.…”
Section: Discussioncontrasting
confidence: 57%
“…In melanoma patients it could be shown that tumor derived changes in the lymph node immune milieu are independent of the existence of lymph node metastases [14]. T-cell polarization and several immune tolerance markers did not differ between metastatic sentinel lymph nodes and tumor free nodes [49]. However, there are immunological alterations in tumor-associated lymph nodes that prepare them for the acceptance of tumor cells and are a prerequisite for metastatic tumor growth [14,49].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in expression of these markers between SNs with and without metastases, suggesting that changes in regional immunity can precede metastasis. 56 A prospective study of Foxp3 + regulatory T cells and DCs in melanoma SNs showed correlations between node positivity and increased regulatory T cells or decreased dendritic cells. 57 Vallacchi et al, 58 using gene expression profiling of melanoma SNs and by unsupervised analysis of gene expression profiles, found "immune response" to be a major gene ontogeny represented.…”
Section: Evidence Of Sn Immune Modulation In Melanoma and Breast Cancermentioning
confidence: 99%